Consequences of Enlightenment - Cascardi, Anthony J., 1953- (Cambridge University Press, 1999)
What is the relationship between contemporary intellectual culture and the European Enlightenment it claims to reject? In Consequences of Enlightenment, Anthony J. Cascardi revisits the arguments advanced in Horkheimer and Adorno's seminal work Dialectic of Enlightenment. Cascardi argues against the view that postmodern culture has rejected Enlightenment beliefs and explores instead the continuities contemporary theory shares with Kant's theory of judgment. The positive consequences of Kant's failed ambition to bring the project of Enlightenment to completion, he argues, are evident in the aesthetic basis on which subjectivity has survived in the contemporary world.
Keywords: Horkheimer, Max, -- 1895-1973. -- Philosophische Fragmente.; Horkheimer, Max, -- 1895-1973. -- Dialektik der Aufklärung.; Philosophische Fragmente (Horkheimer, Max); Aesthetics -- Political aspects.; Aesthetics, Modern -- 20th century.; Enlightenment.; Aesthetics, Modern.; Esthétique -- Aspect politique.; Esthétique -- 20e siècle.; Siècle des Lumières.; Enlightenment (18th-century western movement); PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- History & Surveys -- General.; Aesthetics, Modern; Aesthetics -- Political aspects; Enlightenment; Philosophie; Rezeption; Aufklärung; Dialektik der Aufklärung (Adorno & Horkheimer); Postmodernisme.; Verlichting (cultuurgeschiedenis); Esthetica.; 1900-1999; Electronic books.